Evaluating the Validity of Portfolio Assessments for Licensure Decisions - Mark Wilson; P J Hallam; Raymond L. Pecheone; Pamela A. Moss (Arizona State University, 2014)
This study examines one part of a validity argument for portfolio assessments of teaching practice used as an indicator of teaching quality to inform a licensure decision.  We investigate the relationship among portfolio assessment scores, a test of teacher knowledge (ETS's Praxis I and II),  and changes in student achievement (on Touchstone's Degrees of Reading Power Test [DRP]).  Key questions are the extent to which the assessment of teaching practice (a) predict gains in students' achievement and (b) contribute unique information to this prediction beyond what is contributed by the tests of teacher knowledge.  The venue for our study is Connecticut State Department of Education's (CSDE) support and licensure system for beginning teachers, the Beginning Educator Support and Training (BEST) program (as it was implemented at the time of our study). We investigated whether elementary teachers' mean effects on their students' reading achievement support the use of BEST elementary literacy portfolio scores as a measure of teaching quality for licensure, using a data set gathered from both State and two urban school district sources.  The HLM findings indicate that BEST portfolio scores do indeed distinguish among teachers who were more and less successful in enhancing their students' achievement. An additional analysis indicated that the BEST portfolios add information that is not contained in the Praxis tests, and are more powerful predictors of teachers' contributions to student achievement gains.